Community-based care models for arterial hypertension management in non-pregnant adults in sub-Saharan Africa: a literature scoping review and framework for designing chronic services - Lucia González Fernández; Emmanuel Firima; Elena Robinson; Fabiola Ursprung; Jacqueline Huber; Alain Amstutz; Ravi Gupta; Felix Gerber; Joalane Mokhohlane; Thabo Lejone; Irene Ayakaka; Hongyi Xu; et al. (BMC, 2022)
Abstract Background Arterial hypertension (aHT) is the leading cardiovascular disease (CVD) risk factor in sub-Saharan Africa; it remains, however, underdiagnosed, and undertreated. Community-based care services could potentially expand access to aHT diagnosis and treatment in underserved communities. In this scoping review, we catalogued, described, and appraised community-based care models for aHT in sub-Saharan Africa, considering their acceptability, engagement in care and clinical outcomes. Additionally, we developed a framework to design and describe service delivery models for long-term aHT care. Methods We searched relevant references in Embase Elsevier, MEDLINE Ovid, CINAHL EBSCOhost and Scopus. Included studies described models where substantial care occurred outside a formal health facility and reported on acceptability, blood pressure (BP) control, engagement in care, or end-organ damage. We summarized the interventions' characteristics, effectiveness, and evaluated the quality of included studies. Considering the common integrating elements of aHT care services, we conceptualized a general framework to guide the design of service models for aHT. Results We identified 18,695 records, screened 4,954 and included twelve studies. Four types of aHT care models were identified: services provided at community pharmacies, out-of-facility, household services, and aHT treatment groups. Two studies reported on acceptability, eleven on BP control, ten on engagement in care and one on end-organ damage. Most studies reported significant reductions in BP values and improved access to comprehensive CVDs services through task-sharing. Major reported shortcomings included high attrition rates and their nature as parallel, non-integrated models of care. The overall quality of the studies was low, with high risk of bias, and most of the studies did not include comparisons with routine facility-based care. Conclusions The overall quality of available evidence on community-based aHT care is low. Published models of care are very heterogeneous and available evidence is insufficient to recommend or refute further scale up in sub-Sahara Africa. We propose that future projects and studies implementing and assessing community-based models for aHT care are designed and described according to six building blocks: providers, target groups, components, location, time of service delivery, and their use of information systems.